2020
DOI: 10.15441/ceem.19.057
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors related with outcomes in traumatic out-of-hospital cardiac arrest patients without prehospital return of spontaneous circulation: a nationwide observational study

Abstract: Objective To evaluate the prognostic factors associated with the sustained return of spontaneous circulation (ROSC) and survival to hospital discharge in traumatic out-of-hospital cardiac arrest (TOHCA) patients without prehospital ROSC. Methods We analyzed Korean nationwide data from the Out-of-Hospital Cardiac Arrest Surveillance, and included adult TOHCA patients without prehospital ROSC from January 2012 to December 2016. The primary outcome was sustained ROSC (> 20 minutes). The secondary outcome was surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Fifty-six articles were excluded for various reasons (Fig. 1 ), resulting in 36 articles being included [ 1 3 , 5 , 6 , 16 47 ]. All studies scored 6 or 7 points on the Newcastle–Ottawa Quality Assessment Scale and therefore no study was excluded for quality reasons (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-six articles were excluded for various reasons (Fig. 1 ), resulting in 36 articles being included [ 1 3 , 5 , 6 , 16 47 ]. All studies scored 6 or 7 points on the Newcastle–Ottawa Quality Assessment Scale and therefore no study was excluded for quality reasons (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most included studies ( n = 21) were published between 2016 and 2019 [ 27 – 47 ], and most of the 36 primary studies were carried out in either Europe ( n = 14) [ 2 , 3 , 6 , 19 – 21 , 28 , 32 , 33 , 35 , 36 , 40 , 44 , 46 ] or Asia ( n = 13) [ 22 , 25 , 26 , 30 , 31 , 34 , 37 39 , 41 , 43 , 45 , 47 ]. Almost all included studies were retrospective cohort studies ( n = 32) [ 1 3 , 16 18 , 20 38 , 40 44 , 46 , 47 ] and included both penetrating and blunt trauma cases ( n = 30) [ 1 3 , 16 , 17 , 19 – 21 , 23 25 , 27 , 28 , 30 36 , 40 47 ]. More detailed characteristics of the included primary studies are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in our study, ROSC before arrival at the ED is a predictor for survival, and longer transport times did not reduce survival-to-discharge when ROSC was observed, indicating continued efforts should be devoted to these cases. Other studies have shown that an [14][15][16][17]. Pulseless electrical activity (PEA) or preserved cardiac wall motion observed by ultrasound examination may also be predictive of survival and can be easily performed in the ED [18].…”
Section: Discussionmentioning
confidence: 99%
“…Neurological outcomes of patients resuscitated from CA are associated with various individual-related factors, such as age, comorbidities, and CA event circumstances, including unwitnessed arrest, cardiac rhythm and time to ROSC at the initial assessment. 14 These factors together with clinical investigations and laboratory/imaging tests at hospital admission might already provide information about an individual’s fate in terms of unfavorable neurological outcomes and mortality. 15 Previous studies have focused on early neurological outcome indicators of comatose post-CA survivors.…”
Section: Discussionmentioning
confidence: 99%